The Effect of Different Types of Walking on Dual-Task Performance and Task Prioritization among Community-Dwelling Older Adults - Maayan Agmon; Einat Kodesh; Rachel Kizony (The Scientific World Journal)
Background. The ability to safely conduct different types of walking concurrently with a cognitive task (i.e., dual task) is crucial for daily life. The contribution of different walking types to dual-task performance has not yet been determined, nor is there agreement on the strategies that older adults use to divide their attention between two tasks (task prioritization). Objectives. To compare the effect of walking in three different directions (forward, backward, and sideways) on dual-task performance and to explore the strategies of older adults to allocate their attention in response to different motor task demands. Design. A cross-sectional study. Subjects. Thirty-two (22 female) community-dwelling older adults (aged 72.7±5.7 years). Methods. Subjects randomly conducted single and dual task: walking to three directions separately, cognitive tasks separately, and combination of the two. Results. Walking forward was the least demanding task, during single (FW < BW, SW) (P<.001) and dual tasks (FW < BW < SW) (P<.001). The calculation of DTC revealed the same pattern (P<.001). DTC of the cognitive tasks was not significantly different among the three walking types. Conclusions. The decline mainly in the motor performance during dual task indicates that participants prioritized the cognitive task. These findings challenge the “posture first” paradigm for task prioritization.